Multiomics approaches reveal a link between the MS4A gene loci, TREM2, and microglia function: Genetics/omics and systems biology. (7th December 2020) - You, Shih‐Feng; He, June; Filipello, Fabia; Brase, Logan; Del‐Aguila, Jorge L.; Mihindukulasuriya, Kathie A.; Benitez, Bruno A.; Cruchaga, Carlos; Harari, Oscar; Karch, Celeste M.
Abstract: Background: Soluble triggering receptor expressed on myeloid cells 2 (sTREM2) in cerebrospinal fluid (CSF) has been associated with Alzheimer's disease (AD). TREM2 plays a critical role in microglial activation, survival, and phagocytosis; however, the pathophysiological role of sTREM2 in AD is not well understood. Understanding the role of sTREM2 in AD may reveal new pathological mechanisms and lead to the identification of therapeutic targets. We recently identified common variants in the membrane‐spanning 4‐domains subfamily A ( MS4A ) gene region that were associated with CSF sTREM2 concentrations. One variant (rs1582763) was associated with increased CSF sTREM2 and reduced AD risk, while a second variant (rs6591561) was associated with reduced CSF sTREM2 and increased AD risk. Using human induced pluripotent stem cell‐derived microglia, we found that MS4A4A and TREM2 colocalize on lipid rafts at the plasma membrane. Here, we sought to define the molecular mechanism by which variants in the MS4A gene region impact sTREM2, microglia function and AD risk. Methods: To define the functional effects of MS4A variants, we used genotype and bulk RNAseq data from 579 human brain samples. We then evaluated microglia specific effects using single nuclei RNAseq data obtained from 70 human brains. Results: Leveraging genotypic and transcriptomic data in human brain tissue, we found that rs1582763 and rs6591561 alter distinct molecular pathways. Rs1582763, which confers AD resilience, impacts pathways associated with cholesterol metabolism, while rs6591561, which confers AD risk, impacts pathways associated with chemokine regulation. Using single nuclei RNAseq data in human brain tissue, we found that variants in the MS4A gene region were sufficient to alter specific microglia populations. Conclusions: These findings also provide a mechanistic explanation for the original GWAS signal in the MS4A locus for AD risk and indicate that TREM2 may be involved in AD pathogenesis not only in TREM2 risk‐variant carriers but also in those with sporadic disease.